Climate impacts on rural sanitation: evidence from Burkina Faso, Bangladesh and Lao PDR - Iyer, Ruhil; Kohlitz, Jeremy (Frontiers in Water, 2024)
Climate change is a real, emerging issue in the rural sanitation sector. In an already stressed context, they threaten sustained sanitation progress and outcomes. Yet, evidence gaps continue to exist on how climate impacts affect rural sanitation and hygiene practices and the narratives of people and households at the forefront, experiencing climate impacts on sanitation in rural areas are largely absent. The sector also needs more thinking on how programming can adapt to consider climate hazards. This paper builds evidence on climate impacts on rural sanitation practices through case studies in Burkina Faso, Bangladesh and Lao PDR. Studies were undertaken through various participatory methodologies to understand and respond to lived experience, differentially experienced impacts and tacit knowledge of climate impacts on rural sanitation. Climate hazards affect sanitation via numerous, dynamic interlinking pathways. The social context and local anthropogenic activities shape how these hazards impact physical access to sanitation infrastructure, access to local resources and markets, and livelihoods needed to support safe sanitation. These impacts include behaviours and practices, infrastructure, and people’s capacity to invest in sanitation. Strong implications have emerged for how sanitation practice, research and policy must evolve to account for climate hazards to ensure sustained sanitation outcomes, systemic resilience and programme delivery. The rural sanitation sector must recognize the various interlinkages and distinct experiences of climate across people’s daily lives as they have cascading impacts on sanitation practice. Climate considerations must be integrated at every stage of sanitation project delivery, and more holistic pathways must be explored, to ensure root causes of systemic issues such as poverty and vulnerability are considered for sustained and transformative outcomes.